2018
DOI: 10.1542/hpeds.2017-0180
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Sepsis Risk Calculator at an Academic Birth Hospital

Abstract: The SRC was integrated into the workflow of a large, academic perinatal center, resulting in significant reductions in antibiotics and laboratory testing for EOS and demonstrating the potential for this approach to impact national practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
78
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 24 publications
7
78
0
3
Order By: Relevance
“…[1][2][3] After our QI practice changes, reductions in laboratory testing and antibiotic exposure were evident when looking across the entire cohort of late preterm and term infants (Fig 2). Our reductions in laboratory testing and antibiotic exposure are similar to those reported after implementation of serial examinations 15 or use of the NSC 13,14 at other centers. Collectively, these experiences indicate that substantial reductions in interventions for infants traditionally deemed at high risk for EOS can be achieved without adverse events.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…[1][2][3] After our QI practice changes, reductions in laboratory testing and antibiotic exposure were evident when looking across the entire cohort of late preterm and term infants (Fig 2). Our reductions in laboratory testing and antibiotic exposure are similar to those reported after implementation of serial examinations 15 or use of the NSC 13,14 at other centers. Collectively, these experiences indicate that substantial reductions in interventions for infants traditionally deemed at high risk for EOS can be achieved without adverse events.…”
Section: Discussionsupporting
confidence: 82%
“…Six patients were ill at birth; the other 4 had NSC risk estimates at birth ,0.3 per 1000 and developed signs of illness between 5 and 20 hours of age. 13 Dhudasia et al 14 reported 4 cases of culture-positive EOS in a cohort of 11 782 births; of these, 1 patient was ill at birth, 1 had a low NSC risk estimate (0.3 per 1000) at birth but developed signs of infection at 36 hours of age, and 2 were treated with antibiotics empirically because of elevated EOS risk estimates at birth (11.45 and 3.41 per 1000, respectively) and never developed signs of illness. These reports reveal the central role of serial clinical evaluations in identifying infected infants even when using the NSC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis is further supported by a recent theoretical costbenefit analysis, which estimated a net monetary benefit of $3998 per infant with a 60% likelihood of net benefit in a US setting [7]. To our knowledge, despite signs of significant uptake [8] and multiple reports on adoption of the EOS calculator [3,9,10], no real-world evidence of the effect of EOS calculator use on financial costs associated with healthcare for suspected EOS has been published.…”
Section: Introductionmentioning
confidence: 69%
“…The classification of infants as clinically ill, equivocal, or well appearing requires ongoing clinical assessment over the first 12 hours after birth. 44,46,48 Workflow changes could be needed to accommodate changes in the frequency of vital signs and other clinical assessments for infants who are identified as being at moderate risk of EOS. Those at institutions opting for this approach may set different risk thresholds for specific actions other than those that are validated 44,48 but should also consider quantifying the effect of the chosen risk thresholds to affirm safety and efficacy.…”
Section: Multivariate Risk Assessmentmentioning
confidence: 99%